Multiple object recognition - Alamin, Sabri Mohammed; Khalifa, Othman Omran (2016)
With the increased processing power and emerging an advanced technologies, industries challenging for more demands for human life. Many algorithms have been proposed to solve the recent unsolved problems of object recognition, however, it still lack of tracking multiple objects in real time. Object detection and recognition in noisy and crowded area is still a challenging difficulty in the area of computer vision. The objective of this system is to identify the different objects using some techniques. Mainly there are three basic steps in video analysis: Detection of objects of interest from moving objects, Tracking of that interested objects in consecutive frames, and Analysis of object tracks to understand their behavior. Simple object detection compares a static background frame at the pixel level with the current frame of video. The existing method in this domain first tries to detect the interest object in video frames. One of the main difficulties in object tracking among many others is to choose suitable features and models for recognizing and tracking the interested object from a video